Temperature Effects on Concrete 1985
DOI: 10.1520/stp34208s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Delivery Time on Concrete Proportions

Abstract: The literature demonstrates that concrete produced at high temperatures [35 versus 18°C (95 versus 65°F)] or mixed and agitated for 90 versus 20 min, tends to have increased mixing water requirements and reduced strength. The research reported here demonstrates that the additional cement required to compensate for this strength loss can be very modest. Concrete was mixed at temperatures of 18 and 35°C (65 and 95°F). Two series of mixtures were proportioned to produce strengths of 28 to 31 MPa (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…The slump measurement results, according to the curing temperature and cement type, showed that every specimen satisfied the target value of 150 ± 25 mm. In general, the higher the concrete temperature and the smaller the unit quantity, the lower the consistency [ 17 , 42 ]; the same trend appeared in this experiment. Thus, to adjust the target slump, the amount of high-performance water-reducing agent was increased as the concrete mixing temperature and design strength increased.…”
Section: Resultssupporting
confidence: 74%
“…The slump measurement results, according to the curing temperature and cement type, showed that every specimen satisfied the target value of 150 ± 25 mm. In general, the higher the concrete temperature and the smaller the unit quantity, the lower the consistency [ 17 , 42 ]; the same trend appeared in this experiment. Thus, to adjust the target slump, the amount of high-performance water-reducing agent was increased as the concrete mixing temperature and design strength increased.…”
Section: Resultssupporting
confidence: 74%
“…The experimental results found that prolonged mixing reduced the workability and increases the compressive strength of the nonre-tempered concrete. Gaynor et al (1985) studied the effect of temperature and delivery time on concrete properties. The experimental results showed that the extended delivery time might have a slight effect on the properties of concrete.…”
Section: Introductionmentioning
confidence: 99%